INFORMATION SYSTEM FOR REQUISITIONING GOODS CV. SADAR GYPSUM - Doni Angga Prabowo; Don Elsyafitra, SKom (Jurnal Sistem Informasi, 2001)
CV. Sadar Gypsum on reservations data recording at each ordering of goods is still done manually resulting in less efficiency of service to consumers. Therefore to improve the quality of service to consumers, the authors try to help CV. Sadar Gypsum in order to improve service quality to consumers with a reservation system dikomputerisasikannya goods. With the computerized system is expected to minimize time and increase service quality to consumers. In this case the authors solve the problem by asking how the proposed procedure along with FOD systems, Diagram Context, Diagram Zero, Entity Relationship Diagram, Normalization, and file structure as well as software by using FoxBase +.